The development of lean muscle, bone and fat in the West African Dwarf goat of Nigeria maintained on good plane of nutrition - Awah, A.A.; Adeleye, I.O.A. (1994)
Thirty West African Dwarf goat kids were raised on good diets intensively from 5 days to 52 weeks of age. Six animals (3 males and 3 females) were serially slaughtered at 2, 8, 12, 24 and 52 weeks of age to study changes in live weight and the development of lean muscle, bone and fat. Lean muscle and fat expressed as the percentage of empty body weight (E.B.W) increased from 31.8% and 3.8% at 2 weeks to 43.2% and 14.2% at 52 weeks respectively. These increases at 52 weeks of age were about 673.2% and 2090.8% over their respective weights at 2 weeks of age. The bone tissue also increased to about 220.7% at 52 weeks over the weight at 2 weeks of age, but decreased from 17.4% E.B.W. at 2 weeks to 9.8% E.B.W at 52 weeks of age. At 2 weeks of age, muscle was the largest tissue, followed by bone, while fat was the least. The bone grew at a low impetus rate, muscle at intermediate rate and fat at high impetus rate so that at 52 weeks of age fat become the second largest tissue and bone the least. Male goat kids entered the rapid fattening phase later in life (about 43 weeks of age) and at heavier live weight (about 12 kg live weight) than the female goat kid (about 28 weeks of age and 9 kg live weight respectively).